Nurse managers' burnout and organizational support: The serial mediating role of leadership and resilience. (14th October 2022) - Luo, Dan; Song, Yulei; Cai, Xue; Li, Ruxue; Bai, Yamei; Chen, Baoyun; Liu, Ya
Abstract: Aims: To investigate the relationship between organizational support and nurse managers' burnout and the serial multiple mediating effects of leadership and resilience. Background: Nurse managers are at a high risk of burnout, especially during the COVID‐19 pandemic. However, no research has been done to examine the associations between nurse managers' organizational support, leadership, resilience and burnout. Methods: This cross‐sectional study recruited 458 nurse managers from 13 tertiary public hospitals in Jiangsu, China. They completed the Survey of Perceived Organizational Support, the Clinical Leadership Survey, the Resilience Scale and the Maslach Burnout Inventor‐Human Service Survey. The serial mediating effect of individual leadership and resilience was estimated using the structural equation modelling method via Mplus 7.0. Results: There were direct and indirect effects of organizational support on burnout, controlling for work variables. Leadership and resilience serially mediate the association between organizational support and burnout ( β = −.051, 95% confidence interval: −0.093 to −0.020). Conclusions: Among nurse managers, organizational support may be sequentially associated with improved leadership first and then resilience, which in turn is related to decreased burnout. Implications for Nursing Management: We recommend that hospital administrators incorporate leadership, resilience and burnout assessment in the routine psychological screening of nurse managers and creatively apply the organizational interventions to decrease nurse managers' burnout.